"Putting a new perspective on life": a qualitative grounded theory of posttraumatic growth following acquired brain injury. Issue 22 (23rd October 2021) - Lyon, Ionie; Fisher, Paul; Gracey, Fergus
Abstract: Purpose: An acquired brain injury (ABI) is often described as a devastating experience and yet positive changes as a result of this event have been described. This study sought to understand the process of developing posttraumatic growth (PTG) following ABI. Method: Semi-structured interviews were conducted with 10 adults with ABI, recruited from three sites of a community day service for people with ABI. Grounded theory was used to explore the development of positive changes experienced as a result of the injury. Results: PTG appeared to occur in a non-linear way as participants negotiated processes captured in the following themes: "living with a life changing injury, " "trying to beat it and acceptance, " "identifying with a new you and others, " and "meaningful positive change." Intra- and inter-personal comparisons emerged as important in accepting changes and reconnecting with pre-injury identity. This seemed to underpin accessing social and practical opportunities giving rise to connection with strengths and growth. Conclusions: This study extends prior research into the process of adjustment and positive outcomes such as growth, although conclusions are limited to this specific sample and context. Further research and clinical practice development addressing acceptance and community engagement to develop positive change following ABI is required. IMPLICATIONS FOR REHABILITATION: Experience of PTG develops over time and influenced by intra-and-inter-personal processes. Acceptance and shared experiences with others may contribute to positive psychological change. Interventions supporting pre-and-post injury comparisons with others could help acceptance. The focus on the management and expression of emotions associated with loss may be beneficial.